Anticipated Effects of Nicotine Reduction on Youth Smoking Initiation and Maintenance. (23rd December 2019) - Colby, Suzanne M; Cassidy, Rachel N; Denlinger-Apte, Rachel; Smith, Tracy T; Pacek, Lauren R; McClernon, F Joseph; Tidey, Jennifer W
Abstract: This commentary summarizes emerging findings on the potential impact of a nicotine reduction policy on youth and young adults. We conclude that: (1) adolescent smokers and nonsmokers alike are likely to be less sensitive to reinforcement from very low nicotine content (VLNC) cigarettes compared with adults; (2) reducing nicotine in cigarettes to 0.4 mg/g would reduce the abuse potential of cigarettes in adolescents and young adults; (3) findings to date do not support concerns that nicotine reduction leads to compensatory smoking in young smokers; and (4) if the scope of a reduced nicotine product standard were applied to all combusted tobacco products, that would likely maximize public health benefit of this policy.